(untitled) - Brookes, A. M. P. (New York, 1966)
Advanced Electric Circuits deals with the concepts of advanced electric circuits and covers topics ranging from the symbolic method of analysis to network theorems, bridge networks, and tuned circuits and filters. Polyphase circuits, non-sinusoidal and transient excitation, and valves and transistors as circuit elements are also discussed, along with elementary transmission-line analysis. Comprised of nine chapters, this book begins with an overview of the j method of solving circuit problems and the various ways in which the vectors can be expressed so that the most suitable form may be chosen for any particular problem. The application of the four basic algebraic processes - addition, subtraction, multiplication, and division - to vectors in the j rotation is also considered. The discussion then turns to bridge networks, tuned circuits and filters, and polyphase circuits. The remaining chapters focus on non-sinusoidal and transient excitation, valves and transistors as circuit elements, and elementary transmission lines. This monograph will be of interest to electricians, electrical engineers, and students of electrical engineering courses.
Keywords: Electric circuit analysis,Phân tích mạch điện